Clothing consumption culture of a neo-tribe: Gay professionals within the subculture of gay consumers. Issue 1 (14th March 2016) - Aung, May; Sha, Ou
Abstract : Purpose: – A number of postmodern consumer scholars have their attention on the consumption behaviour of neo-tribes. Changing gender roles and households' consumption practices have also shaped new sets of cultural manifestations for the clothing consumption milieu. The purpose of this paper is to explore the clothing consumption culture of a neo-tribe, gay professionals within the subculture of gay consumers. Design/methodology/approach: – An extended conceptual framework built upon Ajzen and Fishbein's (1980) theory of "reasoned action" served as the conceptual guideline for this study. Specifically, the attitude-behaviour framework is proposed and employed to better understand the clothing consumption behaviour of a neo-tribe consisting of gay professionals. Personal in-depth interviews were conducted in a metropolitan city as well as two small towns in Canada. Findings: – Stereotypical as well as non-stereotypical understandings are offered. The findings from this study portrayed the gay professions of this neo-tribe as rational and practical. Personal psychological factors, social factors and marketplace factors relevant to a neo-tribe of gay professionals are documented and deeper insights are presented. Research limitations/implications: – Findings challenge the existing understanding of fashion manifestation for this consumers group. However, this study may be of limited scope. Future studies should further examine the clothing consumption cultural manifestations of other neo-tribes within the gay community. Practical implications: – The interviewees consistently demonstrated their positive attitudes towards quality, stylish and conservative clothing. For marketers it is crucial to perceive the gay community as a non-homogeneous market segment. There is a need to understand different consumption practices within this community and to tailor marketing mix elements accordingly. Originality/value: – This study has extended the understanding of the neo-tribes of gay consumers. In addition, this study offers the clothing consumption reality of a neo-tribe encompassing gay professionals. This study illuminates their rational and practical clothing consumption cultural manifestations and clothing consumption behaviour. These insights further enrich the general understandings that exist in the area of consumer research.